2019
DOI: 10.3758/s13414-019-01831-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher attentional costs for numerosity estimation at high densities

Abstract: Humans can estimate numerosity over a large range, but the precision with which they do so varies considerably over that range. For very small sets, within the subitizing range of up to about four items, estimation is rapid and errorless. For intermediate numerosities, errors vary directly with the numerosity, following Weber’s law, but for very high numerosities, with very dense patterns, thresholds continue to rise with the square root of numerosity. This suggests that three different mechanisms operate over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
1
30
0
1
Order By: Relevance
“…Although subitizing was originally thought to be pre-attentive, dependence on attention has become a signature of the subitizing system. Many studies have shown that attention has a much stronger detrimental effect in the subitizing than estimation range, enough to equate subitizing precision and reaction times to those of higher numerosities during dual tasks 10 , 12 , 19 21 . The selective detrimental effect of attentional deprivation in the subitizing range was reinforced by a recent clinical single case study with a simultanagnosic patient (PA) 22 , who suffered a severe visual attentional deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although subitizing was originally thought to be pre-attentive, dependence on attention has become a signature of the subitizing system. Many studies have shown that attention has a much stronger detrimental effect in the subitizing than estimation range, enough to equate subitizing precision and reaction times to those of higher numerosities during dual tasks 10 , 12 , 19 21 . The selective detrimental effect of attentional deprivation in the subitizing range was reinforced by a recent clinical single case study with a simultanagnosic patient (PA) 22 , who suffered a severe visual attentional deficit.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence for interconnection between the systems. Under dual task conditions, sensory thresholds for estimating numerosities in the subitizing range become comparable to those measured in the estimation range, suggesting that the estimation system works even within the subitizing range, but performance for low numbers normally augmented by the automatic deployment of visuo-spatial attentional resources 10 12 . The heavy reliance of subitizing on attention may therefore constitute a characteristic feature of this system and explain its higher precision.…”
Section: Introductionmentioning
confidence: 87%
“…Likewise, reaction-times and sensory thresholds for discriminating extremely high numerosities in the density range are elevated when participants have to respond to a visual distractor task first [42]. On the contrary, numerical discriminations in the estimation range are less affected by the deprivation of visual attentional resources [41][42][43]. A recent study has described a patient with an attentional deficit (simultagnosia) who is highly impaired in discriminating very small and very high numerosities, while thresholds for intermediate numerosities are similar to healthy controls, consistent with the notion that numerical comparisons in the estimation range can be performed with minimal reliance on attentional resources [48].…”
Section: Discussionmentioning
confidence: 99%
“…Subitizing is robust, and occurs for both sequential and simultaneous stimuli, in all sensory modalities 3 , 13 16 . Subitizing is highly dependent on attention 17 24 , and seems to work in parallel with the estimation system, boosting performance at low numerosities.…”
Section: Introductionmentioning
confidence: 99%